Pengembangan Sistem Penangkal Petir dan Pentanahan Elektroda Rod dan Plat - Saini, Makmur; Yunus, A.M. Shiddiq; Pangkung, Andareas (Politeknik Negeri Ujung Pandang, 2016)
The specific objective of this research is to producea system of internallightning and Eksternal lightning rod withgrounding which has been widely used in industries such aslightning protection and grounding system of substation,transmission lines and coupling wire used in high-rise buildingseither belong to government or private property. In this study,lightning rod is located outside the building structure that servesto catch or receive the bolt of lightning and the lightning deliverto the ground safely. In this study there were 5 different depths ofelectrode rod; 3 m, 5 m, 7 m, 9 m, and 12 m, moreover, 5 widevariety of electrode plate that are 1 x 1 m2, 0.75 x 0.75 m2, 0.5 x0.5 m2, 0.35 x 0.35 m2, 0.25 x 0.25 m2. For grounding electrode rod with a depth of 3 m, 5 m, 7 m, 9 m, 12 m in dry conditions grounding resistance values obtained ranged from 1.55 to 2.03 Ohm. For moist soil conditions, grounding resistance values obtained ranged from 2.21 to 2.60 Ohm. For wet soil conditions grounding resistance values obtained ranged from 1.97 to 2.34 Ohm. For grounding plate, R11 and R12 on the dry conditions grounding resistance values obtained ranged from 2.08 to 2.45 Ohm. For moist soil conditions grounding resistance values obtained ranged from 1.88 to 2.18 Ohm. For wet soil conditions grounding resistance values obtained ranged from 1.55 to 2.06 Ohm. On the external lightning rod with two added electrodes with a depth of 12 m and then connected in parallel with the electrode plate to get the smallest value of grounding resistance in accordance with the standards prescribed.